(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the effect of job satisfaction and organizational commitment partially and simultaneously to turnover intentions. The research method used is quantitaive. Research site in Bali Bird Park, Singapadu, Gianyar. The sample was used as many as 67 respondents. The data analysis techniques used are Validity Test, Rehabilitation, Classical Assumptions, Multiple Linear Regression, Determination Coefficient, Multiple Correlation, T Test and Test F. Based on the results of the study obtained the results: (1) job satisfaction has a significant negative effect on turnover intention in employees of Bali Bird Park, Singapadu, Gianyar. (2) Organizational commitment has a significant negative effect on turnover intentions in employees of Bali Bird Park, Singapadu, Gianyar. (3) simultaneous job satisfaction and organizational commitment have a significant effect on turnover intentions in employees of Bali Bird Park, Singapadu, Gianyar. The magnitude of the influence of free variables on turnover intention is 52.3%. The advice in this study is that Bali Bird Park, Singapadu, Gianyar, should foster a relationship between employees and employees with superiors and always look for ways out in case of conflicts within the company. Compensate based on employee performance, create a comfortable work environment, and offer promotional opportunities to qualified employees.